Effects of motivation of the patient on indices of exercise capacity in chronic heart failure. - Clark, A. L. (1994)
BACKGROUND--Measurement of variables of metabolic gas exchange during exercise is widely used to assess the severity of heart failure. The variables derived however, are potentially dependent on motivation of the patient and duration of exercise. METHODS--The data from exercise tests in 23 patients with exertional breathlessness were analysed to derive the following three common indices of exercise tolerance: anaerobic threshold, extrapolated maximum oxygen consumption, and the ventilation to carbon dioxide production slope. The data were reanalysed with the data points from the first 90% of subsequent exercise, the first 75%, and finally the data up to the point where a respiratory gas exchange ratio of 1 was reached. RESULTS--The mean (SEM) anaerobic threshold was lower when computed from 90% of the data points than from 100% (13.2 (1.0) ml/kg/min v 12.5 (1.0), p < 0.001) and lower still from 75% (11.4 (0.7), p = 0.006 v 90%). Extrapolated maximum oxygen consumption was unchanged when computed from 90% of the data, but higher when computed from 75% (25.4 (2.1) ml/kg/min at 100% v 28.6 (2.1) at 75%, p < 0.001). The slope of the ventilation to carbon dioxide production ratio became progressively shallower measured from 90% and 75% of eventual exercise: 32.3 (1.5) from 100% v 30.0 (1.5) from 90%, p < 0.001; and 28.3 from 75%, p < 0.001 v 90%. At a respiratory gas exchange ratio of 1, extrapolated oxygen consumption was unchanged from the final calculation, anaerobic threshold was lower than at 100% of exercise (11.8 (0.9), p = 0.005) and the ventilation to carbon dioxide production slope was shallower (27.5 (1.4), p < 0.001). CONCLUSIONS--Anaerobic threshold tends to overestimate severity of exercise limitation and extrapolated maximum oxygen consumption and the ventilation to carbon dioxide production slope tend to underestimate severity. Extrapolated maximum oxygen consumption is the most reliable of the three measures, and is independent of effort provided that patients are encouraged to exercise to the point where the respiratory gas exchange ratio exceeds 1.